Citizen science data as an efficient tool for mapping protected saproxylic beetles. (April 2017) - Zapponi, L.; Cini, A.; Bardiani, M.; Hardersen, S.; Maura, M.; Maurizi, E.; Redolfi De Zan, L.; Audisio, P.; Bologna, M.A.; Carpaneto, G.M.; Roversi, P.F.; Sabbatini Peverieri, G.; et al.
Abstract: Global change imposes rapid assessments to obtain reliable and updated distribution data to implement conservation measures. This task is undoubtedly unaffordable for numerous invertebrate species, both in terms of time and economic resources, because they are often elusive, detectable life stages are present for a restricted time and ecological data are scarce. Citizen science might be able to provide a large number of records and these data might facilitate the evaluation of extinction risks. Large saproxylic beetles represent an ideal group to assess the potential of citizen science to map distributions on a large scale geographic distribution. The data presented were collected during a citizen science program developed within the LIFE Project "Monitoring of Insects with Public Participation", which used a website and a mobile app to involve citizens. We selected three pan European species protected under the Habitats Directive: Lucanus cervus, Morimus asper / funereus and Rosalia alpina, and we compared the data gathered by the citizen science project with distributional data from the official national species inventory. For all species we found a low overlap of occupied cells and the integration of the two datasets resulted in an increase in the distributional ranges of up to one third. Furthermore, taking into account the time frame of data collection, we found that the extent of occurrence obtained in 10 years of records present in the national dataset was comparable to data collected in only two years of the citizen science data project. Similar results were obtained for the estimates of spatial parameters for the IUCN Red List assessment. Our study shows the potential and the efficacy of citizen science projects as rapid tools to provide reliable distributional data for neglected species of high conservation priority. Highlights: Updated species distributions are fundamental to evaluate extinction risks. Invertebrates are underrepresented in international conservation measures. Citizen science (CS) provided new range data on the saproxylic target species. α-hulls obtained with 2 years of CS and 10 years of inventory data are comparable. CS rapidly provides data to assess the distribution of species of high conservation priority.